2009
DOI: 10.1093/humrep/dep181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gonadotrophin releasing hormone analogues on human endometrial stromal cells and embryo invasion in vitro

Abstract: We suggest that GnRH analogues affect neither the capacity of the endometrium to support invasion nor the invasive potential of the blastocyst in the early stages of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…In this respect it is noteworthy that aromatase cytochrome P450, the enzyme that catalyses the conversion of androgens to oestrogens, is overexpressed in women with endometriosis and adenomyosis, and that therapy with GnRHa decreases expression of aromatase cytochrome P450 in the eutopic endometrium of women with adenomyosis and endometriosis (Ishihara et al, 2003). This effect has been recently confirmed in women with endometriosis by Kim et al (2009). It has also been shown that GnRHa do not significantly influence the extent of decidualization of endometrial stromal cells derived from fertile women during the implantation window; furthermore, they seem to have no adverse effect on human blastocyst invasion (Klemmt et al, 2009). In addition, GnRHa can suppress the expression of nitric oxide synthases and, as a consequence, the generation of peroxynitrite in women with adenomyosis.…”
Section: Medical and Combined Medico-surgical Treatmentmentioning
confidence: 95%
“…In this respect it is noteworthy that aromatase cytochrome P450, the enzyme that catalyses the conversion of androgens to oestrogens, is overexpressed in women with endometriosis and adenomyosis, and that therapy with GnRHa decreases expression of aromatase cytochrome P450 in the eutopic endometrium of women with adenomyosis and endometriosis (Ishihara et al, 2003). This effect has been recently confirmed in women with endometriosis by Kim et al (2009). It has also been shown that GnRHa do not significantly influence the extent of decidualization of endometrial stromal cells derived from fertile women during the implantation window; furthermore, they seem to have no adverse effect on human blastocyst invasion (Klemmt et al, 2009). In addition, GnRHa can suppress the expression of nitric oxide synthases and, as a consequence, the generation of peroxynitrite in women with adenomyosis.…”
Section: Medical and Combined Medico-surgical Treatmentmentioning
confidence: 95%
“…Conversely, primates undergo interstitial implantation, where the syncytial trophoblast formed near the inner cell mass adheres to the uterine epithelium and penetrates into the stroma by intruding between endometrial epithelial cells (Nimbkar-Joshi et al, 2009). In humans, specific interactions such as apposition and early embryo attachment to the uterine epithelium are difficult to observe, due to the tenuous and transient nature of these mechanisms, and investigations rely on biopsies obtained during the estimated time of embryo attachment, or at predicted times in the menstrual cycle (Klemmt et al, 2009;Sela et al, 2013). There is a distinct lack of knowledge regarding the specific mechanisms underlying the early stages of implantation, and as the human implantation site is inaccessible in vivo, in vitro models are increasingly being developed and relied upon (Mardon et al, 2007).…”
Section: The Need To Develop Novel Research Methodologymentioning
confidence: 99%
“…In vitro models of human implantation have been developed using tissues acquired by hysterectomy or endometrial biopsy. These tissues can be cocultured with trophoblast cells from embryos to investigate embryo positioning and invasion (Kliman et al, 1990;Landgren et al, 1996;Klemmt et al, 2009;Chillakuri et al, 2010). While endometrial tissue explants can be cultured in appropriate media to mimic the in vivo endometrial environment, tissue explant models are associated with the major problem of extensive tissue necrosis, thus prompting the use of cell lines as a more promising avenue.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…A recent study using endometrial stromal cells derived from fertile women during implantation window demonstrated that GnRH agonist or antagonist had no detrimental effect on trophoblast invasion and stromal cell decidualization in vitro. However, the elevated levels of GnRH receptors in decidualized stromal cells suggested a function for the GnRH-GnRH receptor pathway in these early implantation events (35).…”
Section: Regulation Of Implantationmentioning
confidence: 99%